2013
DOI: 10.1530/edm-13-0001
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing hypercalciuric kidney stones after treating underlying acromegaly

Abstract: SummaryA 53-year-old male presented with recurrent calcium oxalate kidney stones as a first sign of underlying acromegaly, which vanished when his acromegaly was controlled. The exact mechanism behind hypercalciuria and urolithiasis in acromegaly is not yet clear. By discussing this case, a short overview of the pathophysiology of hypercalciuria in acromegaly and practical insights are given.Learning points Hypercalciuria is a common finding in acromegaly.There are only few reports describing hypercalciuric ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In 57 newly diagnosed ACRO, hypertension was detected in 16 (28.1%) patients. Renal resistive index (RRI), an index that can reveal vascular and functional kidney abnormalities, was found to be higher in hypertensive compared to normotensive patients (p = 0.001), and, in regression analysis, IGF-1 was found to be independently associated with RRI [45]. Since RRI could be a preclinical index of hypertension and could be an early sign of hypertension development, renal Doppler US could be a useful exam in ACRO, especially given its non-invasive and costeffective nature.…”
Section: Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…In 57 newly diagnosed ACRO, hypertension was detected in 16 (28.1%) patients. Renal resistive index (RRI), an index that can reveal vascular and functional kidney abnormalities, was found to be higher in hypertensive compared to normotensive patients (p = 0.001), and, in regression analysis, IGF-1 was found to be independently associated with RRI [45]. Since RRI could be a preclinical index of hypertension and could be an early sign of hypertension development, renal Doppler US could be a useful exam in ACRO, especially given its non-invasive and costeffective nature.…”
Section: Kidneymentioning
confidence: 99%
“…Serious kidney involvement could be circumspect of acromegaly, in particular recurrent nephrolithiasis. Van der Valk et al suspected, and finally made a diagnosis of, acromegaly in a 53-year-old male who had excreted almost one renal calcium oxalate stone per month for the 18 months prior to diagnosis [45]. In a recent study, Bankir et al evaluated tissue elasticity in 40 ACRO compared to 20 healthy controls using share wave elastography (a non-invasive method that can give a quantitative measure of tissue elasticity), in organ size.…”
Section: Kidneymentioning
confidence: 99%
“…Another study by van der Valk et al demonstrated the case of a 53-year-old male with recurrent kidney stones containing calcium oxalate. This was also one of the first symptoms of acromegaly, which subsequently resolved with proper treatment—somatostatin analogs followed by surgery [ 57 ].…”
Section: Discussionmentioning
confidence: 99%